2020
DOI: 10.1007/s40097-019-00330-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Chicory leaf powder and its application as a nano-native plant sorbent for removal of Acid Blue 25 from aqueous media: isotherm, kinetic and thermodynamic study of the adsorption phenomenon

Abstract: In this study, the Chicory leaf powder (CLP) was used as a native adsorbent to eliminate the Acid Blue 25 dye from aqueous media. The prepared native adsorbent was characterized by several techniques including the X-ray powder diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform spectroscopy (FTIR), Brunauer-Emmet-Teller essay (BET), and particle size analyzer (PSA). A collection of experiments was performed to distinguish the optimal conditions and to probe the effects of the different par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…3 c revealed that the pH point of zero charge (pH PZC ) of MWCNTs-KIAgNPs was obtained as 6. This indicates that the surface of MWCNTs-KIAgNPs was positively charged at pH PZC < 6, while the adsorbent surface was negatively charged at pH PZC > 6 15 . In all, pH 6 was selected for further investigation of Cd(II), Ni(II) and Fe(II) adsorption, while pH 3 was utilized for Cr(VI) adsorption due to its optimal adsorption values for all the metal ions without precipitation to metal hydroxides 59 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…3 c revealed that the pH point of zero charge (pH PZC ) of MWCNTs-KIAgNPs was obtained as 6. This indicates that the surface of MWCNTs-KIAgNPs was positively charged at pH PZC < 6, while the adsorbent surface was negatively charged at pH PZC > 6 15 . In all, pH 6 was selected for further investigation of Cd(II), Ni(II) and Fe(II) adsorption, while pH 3 was utilized for Cr(VI) adsorption due to its optimal adsorption values for all the metal ions without precipitation to metal hydroxides 59 .…”
Section: Resultsmentioning
confidence: 93%
“…However, these techniques possess different limitations such as low efficiency, high cost, generation of toxic byproducts, delay in operation, inefficiency in targeting specific pollutants and complexity of treatment methods 12 . Of these techniques, adsorption technology has been identified as one of the most efficient and commonly used treatment method due to its ease of operation control, regeneration potentials, cost efficient, inertness to materials, lack of sludge formation and variety of adsorbents 13 15 . In recent years, nanomaterials have attracted the attention of researchers due to their unique physicochemical properties attributable to their small size, shape, dimensions, large surface area, crystallinity and composition 16 .…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with several studies that indicated a decrease in the specific surface area and pore size of plant powder that was not treated physically or chemically. The specific surface area ranged between 0.48-10.9 m 2 / g (25,26,27,28,29), and the total pore size ranged between 0.0002-0.11 cm 3 /g (30,31,32,33,34), and the average pore diameter of Pistacia vera shell powder was 0.77 nm (30) and Prunus dulcis leaves 3.713 nm (33) and Arundo donaxn plant 4.320 nm (18).…”
Section: Determination Of the Surface Area Of Plant Powder According ...mentioning
confidence: 99%
“…Chicory is also a widely accepted 'medicinal herb' and many communities know its medicinal uses. It is majorly grown in Europe, North America, Asia, some parts of Africa and Egypt, Iran and other regions of the globe [13][14][15]. In Asia and Europe, various preparation of chicory is helpful to cure wide level of diseases including the healing of wound and diabetes, and in Chile, it is consumed as 'winter vegetable' [16].…”
Section: Cichorium Intybus As Ethnic Herbmentioning
confidence: 99%